GEOCHEMISTRY AND GENESIS OF ALKALINE BASALTOIDS IN THE SOUTHERN URALS - Murav'eva N.S.; Senin V.G.; Tevelev Al.V. (My University, 2004)
The composition of rock-forming minerals was analyzed and the crystallization conditions of phe-nocrysts were evaluated for the Paleozoic alkaline volcanic rocks from the Southern Ural, where these rocks are combined in the Mt. Sheludivaya absarokite-shonkinite volcano-plutonic association and the Early Carboniferous Berezino volcanic complex. The high values of Mg# (up to 0.72) of the basalts, their elevated Cr and Ni concentrations (up to 685 and 311 ppm, respectively), and the elevated Cr2O3 contents in clinopyroxene phe-nocrysts testify to the mantle provenance of the melts that produced these rocks. The calculated crystallization temperatures of the clinopyroxene correspond to the basalt liquidus temperatures (1230-1270degreesC). The total pressure was estimated, based on the jadeite distribution between the phenocrysts and rocks, at 5-10 kbar, which corresponds to depths of 15-30 kin, i.e., an intermediate magmatic chamber located within the crust or the uppermost mantle. The high values of the Ba/La and La/Nb ratios (112-130 and 1.50-4.55, respectively) of the rocks of the Mt. Sheludivaya Complex are typical of island-arc alkaline rocks. The La/Yb ratios are quite high (5.5) and also close to those of island-arc shoshonite series. The elevated concentrations of Rb, Ba, Sr, and K of the volcanic rocks at Zr, Nb, Ti, and Y concentrations lower than in oceanic tholeiites can be explained by the enrichment of the source of these rocks in the process of the subduction of the ancient oceanic crust.